EMPLOYEE PERFORMANCE IS ENHANCED BY EMOTIONAL INTELLIGENCE AND JOB SATISFACTION - Sutrisno Sutrisno; Hendry Kurniawan; Ade Risna Sari; Irwan Budi Tarwanto; Muhammad Fatkhurohman Albashori (SEAN Institute, 2022)
Professional human resources are needed in an organization to achieve goals. Professionalism will be seen from employee performance which is influenced by emotional intelligence and employee job satisfaction. Likewise at the Office of the Bandung Regency Diskoperindag, the problem is that the number of employees is lacking in completing work, the quality of work produced by employees is still low, the productivity of innovation organizations is low, and morale is decreasing. The research method uses the census method and data analysis using Multiple Linear Regression .The population and sample are all employees/employees of the Bandung Regency Diskoperindag as many as 117 employees with permanent employee status (ASN). The aim of this study was to determine the effect of emotional intelligence and job satisfaction on employee performance.